Reviewing How Individual Differences in Working Memory Capacity Affect the Ability in Following Instructions - Mohamad Azhari, Abu Bakar; Kartini, Abd Ghani; Norehan, Zulkiply (Secholian Publication, 2023)
This literature review aims to analyze the role of individual differences in working memory capacity in following instructions based on theoretical perspectives and empirical evidence. Individual differences in working memory capacity have an impact on the encoding, and retrieval stage. In general, the output from the review stated that the performance difference between individuals relates to the experimental design and treatment, which include delivery of the instructions, presentation of objects, the length of instructions, involvement of dual tasks, and retrieval methods. In addition, the contents of instructions can be transferred into working memory space if the individuals can give a high level of attention and control the attention to suppress the distractors. Therefore, the ability to follow instructions depends on the individual's understanding of the instructions' meaning and matching them with the available space of their working memory (capacity). This review also adds value and suggestions to the need to conduct more research on the role of working memory capacity in following instructions.